2021
DOI: 10.1021/acsnano.1c09446
|View full text |Cite
|
Sign up to set email alerts
|

Sulfide with Oxygen-Rich Carbon Network for Good Lithium-Storage Kinetics

Abstract: Transition metal sulfides are of great interest as electrode material for alkali metal-ion batteries due to their high theoretical capacity. However, sluggish ion migration and electron transfer kinetics lead to poor cycling stability and rate performance, which hinders their practical applications. Herein, we develop a two-step localized carbonization and sulfurization method to construct a CoS2 composite material (CoS2@CNTs@C) from an in situ integrated zeolitic imidazolate framework (ZIF-67) and multiwalled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 68 publications
(105 reference statements)
0
8
0
Order By: Relevance
“…Two broad diffraction peaks at 26.1° and 44.4° in CC, CC@ZIF-67, and CC@CoS 2 /MoS 2 were assigned to the (002) and (100) reflections of graphite, respectively (JCPDS 41–1487) . After the sulfurization process, the typical peaks of ZIF-67 vanished from the sample of CC@ZIF-67 with the emergence of a series of peaks located at 14.4° and 32.3°, 36.2°, 39.8°, and 54.9°, respectively corresponding to the MoS 2 (JCPDS 37–1492) and CoS 2 (JCPDS 41–1471), , suggesting the successful synthesis of the heterojunction CC@CoS 2 /MoS 2 (Figure a). The composition of the C, S, Co, and Mo elements was confirmed by using X-ray photoelectron spectroscopy (XPS), which was used to observe the surface elemental component and the chemical state of elements for CC@CoS 2 /MoS 2 (Figure b).…”
Section: Resultsmentioning
confidence: 99%
“…Two broad diffraction peaks at 26.1° and 44.4° in CC, CC@ZIF-67, and CC@CoS 2 /MoS 2 were assigned to the (002) and (100) reflections of graphite, respectively (JCPDS 41–1487) . After the sulfurization process, the typical peaks of ZIF-67 vanished from the sample of CC@ZIF-67 with the emergence of a series of peaks located at 14.4° and 32.3°, 36.2°, 39.8°, and 54.9°, respectively corresponding to the MoS 2 (JCPDS 37–1492) and CoS 2 (JCPDS 41–1471), , suggesting the successful synthesis of the heterojunction CC@CoS 2 /MoS 2 (Figure a). The composition of the C, S, Co, and Mo elements was confirmed by using X-ray photoelectron spectroscopy (XPS), which was used to observe the surface elemental component and the chemical state of elements for CC@CoS 2 /MoS 2 (Figure b).…”
Section: Resultsmentioning
confidence: 99%
“…Oxygen functional groups can provide opportunities to further improve the electrochemical performance, and abundant oxygen functional groups can provide additional capacitive adsorption sites for metal ions, which can significantly increase the capacity. [175][176][177][178] Lu's research group proposed that the C-O bond participates in the Zn storage process by forming C-O-Zn with Zn 2+ , while the additional N doping can significantly promote the chemisorption of Zn 2+ . 179 Shao et al demonstrated that carboxyl and carbonyl groups can significantly improve Zn 2+ chemisorption, pseudocapacitive redox activity, and aqueous electrolyte wettability.…”
Section: Role Of Oxygen Functional Groupsmentioning
confidence: 99%
“…However, CoS 2 electrode is suffering from the volume expansion and pulverization during work, resulting in poor cycle and rate performance, which hinder its widespread application. [6][7][8][9] Recently, significant attempts have been made to overcome the issues. As reported, carbonbased compounds could ensure the LIBs working better by reducing volume expansion during the cycle process and promoting rapid electron transfer.…”
Section: Introductionmentioning
confidence: 99%